Redesign of Rupture Disc Cross-Cut Type on the Condenser Steam Turbine Using Aluminium Alloy 1100 Materials - Marwan; Alief Wikarta (Syntax Corporation, 2026)
In 2018, the electrical power system in South Sumatra experienced a major disturbance that caused a widespread blackout affecting all power plants, including the Indralaya Combined Cycle Power Plant (CCPP). To protect condenser system equipment from overpressure conditions, a rupture disc is installed as a safety device. The rupture disc must withstand the condenser operating vacuum pressure while rupturing in a controlled manner under excessive pressure conditions. This study aims to redesign and evaluate a safe and effective rupture disc using numerical simulation, analytical calculation, and experimental testing. Numerical analysis was conducted using the Finite Element Method (FEM) in ANSYS with a static structural approach. Analytical burst pressure prediction was performed using the Salarvand equation. Experimental validation was carried out through vacuum pressure testing on the actual rupture disc and overpressure testing on a 1:10 scale prototype. The results indicate that groove depth and scoring pattern significantly influence the burst pressure of the rupture disc. Increasing groove depth decreases burst pressure due to higher stress concentration in the grooved region. Experimental testing showed that the rupture disc with a groove depth of 1.5 mm failed before reaching the operating vacuum pressure of −0.086 bar, whereas the 0.5 mm groove depth maintained structural integrity under the same condition. Validated numerical simulation results demonstrated that rupture discs with groove depths of 0.5 mm and 1.0 mm produced burst pressures ranging from 0.10 to 0.12 MPa under overpressure conditions. The redesigned rupture disc therefore meets condenser safety requirements and has potential as a lower-cost alternative to OEM components using locally available materials.